Systematic literature review of the research design based on fatwa methods - Siti Aishah Zainuddin; Shahir Akram Hassan; Wan Mohd Khairul Firdaus Wan Khairuldin (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study conducted a systematic literature review on the fatwa-based research design. The fatwa process seen can be utilized when building a research design in Islamic-based research methods. There is yet to be a systematic literature review conducted on existing studies regarding a research design based on the fatwa process. Can the f atwa method be applied as an Islamic-based research design? The objectives were to identify and analyse literature related to fatwa and research designs in Islamic-based research by using the systematic literature review method. Based on ROSES publication standards, three databases, namely Scopus, Google Scholar and Dimensions, were chosen to search for articles dating from 2014 to 2020. A total of 824 reference materials containing the keywords ‘research design’, ‘research’ and ‘fatwa’ were found, but only 10 were analysed after passing the quality appraisal process. This study found three themes, namely Islamic research methods, research design elements and the fatwa method. Construction of the fatwa-based research design is a new branch of science still in its early stages and requires extensive research. Therefore, this study suggests that the desired research design should rely on Islamic tasawur and epistemology, which is based on the fatwa method and uses the systematic literature review method.